Autofluorescence imaging of human RPE cell granules using structured illumination microscopy - Ach, Thomas; Best, Gerrit; Roßberger, Sabrina; Cremer, Christoph; Dithmar, Stefan (British journal of ophthalmology, 2012)
Background/aims To characterise single autofluorescent (AF) granules in human retinal pigment epithelium (RPE) cells using structured illumination microscopy (SIM). Methods: Morphological characteristics and autofluorescence behaviour of lipofuscin (LF) and melanolipofuscin (MLF) granules of macular RPE cells (66-year-old donor) were examined with SIM using three different laser light excitation wavelengths (488, 568 and 647 nm). High-resolution images were reconstructed and exported to Matlab R2009a (The Mathworks Inc, Natick, MA, USA) to determine accurate size and emission intensities of LF and MLF granules. Results: SIM doubles lateral resolution compared with conventionally used wide-field microscopy and allows visualisation of intracellular structures down to 110 nm lateral resolution. AF patterns were examined in 133 LF and 27 MLF granules. LF granules (968±220 nm) were significantly smaller in diameter than MLF granules (1097±110 nm; p<0.001). LF granules showed an inhomogeneous intragranular pattern, and the average intensity negatively correlated with the size of these granules when excited at 647 nm. The autofluorescence of MLF granules was more homogeneous, but shifted towards higher excitation wavelengths in the centre of the granules. Conclusion: SIM is a useful tool for examining AF signals within single LF and MLF granules in RPE cells. This allows new insights into RPE autofluorescence patterns.